The FLARE™ Intraoperative Near-Infrared Fluorescence Imaging System: A First-in-Human Clinical Trial in Breast Cancer Sentinel Lymph Node Mapping - Troyan, Susan L.; Kianzad, Vida; Gibbs-Strauss, Summer L.; Gioux, Sylvain; Matsui, Aya; Oketokoun, Rafiou; Ngo, Long; Khamene, Ali; Azar, Fred; Frangioni, John V. (Annals of surgical oncology, 2009)
Background Invisible NIR fluorescent light can provide high sensitivity, high-resolution, and real-time image-guidance during oncologic surgery, but imaging systems that are presently available do not display this invisible light in the context of surgical anatomy. The FLARE ™ imaging system overcomes this major obstacle. Methods Color video was acquired simultaneously, and in real-time, along with two independent channels of NIR fluorescence. Grayscale NIR fluorescence images were converted to visible “pseudo-colors” and overlaid onto the color video image. Yorkshire pigs weighing 35 kg (n = 5) were used for final preclinical validation of the imaging system. A six-patient pilot study was conducted in women undergoing sentinel lymph node (SLN) mapping for breast cancer. Subjects received 99m Tc-sulfur colloid lymphoscintigraphy. In addition, 12.5 μg of indocyanine green (ICG) diluted in human serum albumin (HSA) was used as an NIR fluorescent lymphatic tracer. Results The FLARE ™ system permitted facile positioning in the operating room. NIR light did not change the look of the surgical field. Simultaneous pan-lymphatic and SLN mapping was demonstrated in swine using clinically available NIR fluorophores and the dual NIR capabilities of the system. In the pilot clinical trial, a total of nine SLNs were identified by 99m Tc- lymphoscintigraphy and nine SLNs were identified by NIR fluorescence, although results differed in two patients. No adverse events were encountered. Conclusions We describe the successful clinical translation of a new NIR fluorescence imaging system for image-guided oncologic surgery.